Evaluasi Diri Guru Bahasa Jepang terhadap Penguasaan Modul Ajar dan ATP berdasarkan Kurikulum Merdeka - Dwi Puspitosari; Ai Sumirah Setiawati; Heni Hernawati (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2023)
ABSTRACTThis series of service activities has been carried out in collaboration between the service team and the Japanese Language MGMP of Central Java province. A preliminary study was conducted to find out the latest information regarding the urgent needs of Japanese language teachers in Central Java. Based on the information obtained, the problem faced is the lack of assistance from teaching practitioners in creating teaching modules and the flow of learning objectives which must be adapted to the Merdeka Curriculum. Assistance in creating teaching modules and seminars was carried out in 3 meetings. During mentoring, participants are given an understanding of the differences between the old curriculum and the Merdeka Curriculum in terms of competency achievements and the roles of teachers and students in teaching and learning activities. It is hoped that this activity can help Japanese teachers in the initial process of teaching to learning evaluation. Seminar activities regarding the differences in the application of the Merdeka Curriculum in high schools and universities are expected to equip high school students and teachers to prepare to continue learning Japanese at the tertiary level, as well as equip Japanese Language Education students and lecturers who will guide PLP, so that they can become more familiar with the application of the Merdeka Curriculum in Senior High School. Keywords: Teaching Module, Flow of Learning Objectives, Merdeka Curriculum, Japanese language learning ABSTRAKSerangkaian kegiatan pengabdian ini telah dilaksanakan dengan kerja sama antara tim pengabdian dan MGMP Bahasa Jepang provinsi Jateng. Studi pendahuluan dilakukan untuk mengetahui informasi terkini mengenai kebutuhan mendesak para guru bahasa Jepang di Jawa Tengah. Berdasarkan informasi yang didapat masalah yang dihadapi adalah minimnya pendampingan dari praktisi pengajar dalam pembuatan modul ajar dan alur tujuan pembelajaran yang harus disesuaikan dengan Kurikulum Merdeka. Pendampingan pembuatan modul ajar serta seminar dilaksanakan dalam 3 kali pertemuan. Saat pendampingan, peserta diberikan pemahaman mengenai perbedaan kurikulum lama dan Kurikulum Merdeka dalam hal capaian kompetensi dan peran guru dan siswa dalam kegiatan belajar mengajar. Kegiatan ini diharapkan dapat membantu guru bahasa Jepang dalam proses awal pengajaran hingga evaluasi pembelajaran. Kegiatan seminar tentang perbedaan penerapan Kurikulum Merdeka di SMA dan Perguruan Tinggi diharapkan membekali siswa dan guru SMA untuk persiapan melanjutkan pembelajaran bahasa Jepang di tingkat perguruan tinggi, serta membekali mahasiswa dan dosen Pendidikan Bahasa Jepang yang akan membimbing PLP, agar dapat lebih mengenal penerapan Kurikulum Merdeka di SMA. Kata Kunci: Modul Ajar, Alur Tujuan Pembelajaran, Kurikulum Merdeka, Pembelajaran bahasa Jepang